Estimation of genetic parameters using spatial analysis of Pinus elliottii Engelm. var. elliottii second-generation progeny trials in Argentina - Belaber, Ector C. (2018)
Non-spatial and spatial analyses were carried out to estimate genetic parameters for growth and stem straightness traits between ages 4 and 7 in two series of eight progeny trials of Pinus elliottii Engelm. var. elliottii (PEE) established in 2004 and 2008, comprising 429 open-pollinated families from Instituto Nacional de Tecnología Agropecuaria (INTA) tree breeding population in Argentina. A first-order autoregressive spatial mixed model was found to significantly improve the fit of the model, compared with the standard non-spatial mixed model approach, due to substantial spatial heterogeneity within sites. The average individual-tree narrow-sense heritability estimates based on this spatial analysis were 0.49 for diameter at breast height, 0.36 for total height, and 0.48 for volume, with stem straightness being low to moderate (average = 0.11). The additive genetic correlation estimates between growth traits were positive (0.51 ≤  r^a  ≤ 0.99) and statistically significant from zero. In contrast, the genetic correlations between growth traits and stem straightness although in general also positive were not significantly different from zero (− 0.22 ≤  r^a  ≤ 0.59). Age-to-age genetic correlations were consistently higher for growth traits ( r^a  ≥ 0.81) than for stem straightness ( r^a  ≥ 0.33). The average additive genetic correlation estimated between sites within test series was high for all traits evaluated (average > 0.72). In contrast, average additive genetic correlation estimated between sites across series was slightly lower (average < 0.63). Implications of all these parameter estimates for genetic improvement of PEE in Argentina are discussed.